User-centred digital solution for dentofacial deformities management: an innovative approach technology based - Abbate, Vincenzo; Carraturo, Emanuele; Togo, Giulia; Troise, Stefania; Calabrìa, Federica; Cataldi, Mauro; Adamo, Daniela; Iaccarino, Guido; Illario, Maddalena; Nocini, Riccardo; Dell'Aversana Orabona, Giovanni (Frontiers in Digital Health, 2025)
ObjectiveDentofacial deformities (DFD) encompass a range of conditions affecting approximately 60% of the population, varying from mild to severe cases. Managing these disorders requires a multidisciplinary approach, yet establishing a unified therapeutic protocol across different specialties often proves challenging. This underscores the necessity to understand the specific needs and demands of patients diagnosed with DFD, aiming to develop an effective treatment pathway. The objective of our study is to identify the unmet needs of patients with DFD and to propose digital solutions, based on Information and Communication Technology (ICT), that can help patients meet these needs by improving the diagnostic-therapeutic pathway.MethodsBy examining the medical records of 147 patients diagnosed with DFD, a team of specialists created the profile of a hypothetical DFD patient, termed “Persona” by using the “Blueprint- persona”. This Persona theoretically represents the broader DFD patient population, capturing their needs, demands, goals, problems, and challenges. Based on these findings, a comprehensive ‘DFD Management Pathway’ is proposed, encompassing both general and specialized preoperative and postoperative consultations required for these patients.ResultsThe identified unmet needs of a typical DFD patient were psychological support, nutritional support and diet recommendations, advice on oral hygiene, assistance by specialized professionals. The proposed digital solutions were the use of video tutorials and online courses, daily notifications on applications on smartphones, social media channel and multidisciplinary platform.ConclusionThis study highlights that the Blueprint methodology proves instrumental in pinpointing specific characteristics and unmet needs of various patient groups. The critical gaps in the diagnostic-therapeutic pathway for patients with dentofacial deformities and underscores the potential of digital solutions in addressing these unmet needs. By creating a detailed patient Persona, by using The Blueprint methodology, and mapping their challenges, psychological support, nutritional guidance, oral hygiene advice have been identified as unmeet needs. The proposed digital tools, including video tutorials, online courses, smartphone notifications, social media channels, and multidisciplinary platforms, provide a promising avenue to enhance patient engagement, streamline care delivery, and improve overall treatment outcomes. Future research should focus on validating these solutions in clinical settings to ensure their feasibility and effectiveness in addressing the unique demands of DFD patients.